2021
DOI: 10.4085/1062-6050-0588.20
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular/Ocular Motor Screening Assessment Outcomes After Sport-Related Concussion in High School and Collegiate Athletes

Abstract: Context: Vestibular and ocular motor assessment is an emerging clinical assessment for sport-related concussion (SRC). The increased use of these assessments by clinicians calls for examination of outcomes in populations that may impact clinical practice. Objective: Compare vestibular and ocular motor impairments in high school and collegiate athletes within 72 hours of SRC. Second, examine the distribution of impairments in these populations based upon pre-established clinical cut-off scores. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Table 1 provides an overview of studies [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] included in this review. The table lists study design (categorized as per Mathes and Pieper's suggested approach for systematic reviews 19 ) as well as brief highlights of methods and/or findings.…”
Section: Overview Of Studies Included In This Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 provides an overview of studies [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] included in this review. The table lists study design (categorized as per Mathes and Pieper's suggested approach for systematic reviews 19 ) as well as brief highlights of methods and/or findings.…”
Section: Overview Of Studies Included In This Reviewmentioning
confidence: 99%
“…Most data 15,17 indicate VOMS predictive utility does not vary significantly within the age groups evaluated in the existing evidence base. However, the focus of most evidence on high-school or college athletes leaves open the question of generalizability to different age groups.…”
Section: Issues Affecting Interpretation Of the Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Even if the history of concussion group has a significant total change score difference, the athlete in the history of concussion group with the most total change score had a TCS value of 5 on 8 tests, which is negligeable. Recovery of symptom provocation on VOMS have been demonstrated to take 8 days (Glendon et al, 2021) and the total change score to be a better indicator that the total score (Tomczyk et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Performance on these measures may also be influenced by the presence of coexisting injuries such as cervical impairments, 12 , 13 , 14 which can also be associated with dizziness and other visuovestibular symptoms after mTBI. 13 , 14 , 15 Because measures of symptom provocation in response to VOR tasks have more recently started to be used to identify the presence of potential vestibulo-ocular impairments, 16 , 17 , 18 these influences need to be better understood.…”
mentioning
confidence: 99%